Effects of atmospheric and soil drought on growth and development of Hevea brasiliensis - Devakumar A S; Annamalainathan K; Jacob J; Prakash P G; Sathik M B M; Vijayakumar K R (Journal of Rubber Research, 1998)
A field study was conducted in the severely drought prone North Konkan region on the West coast of India where rubber plants (clone RRIM 600) had been grown with and without summer irrigation since 1987. After nine years, trees grown with irrigation had a 32;increase in leaf area index and nearly twice as much sunlight interception by their canopy as the rainfed trees. This led to 52;more shoot biomass per tree in the irrigated treatment. Irrigated trees had theicker bark and most of that was present as soft bark. At the end of the seventh and eighth year, 78;and 97;of the irrigated trees erew ready for tapping respectively, suggesting fast and uniform growth of the trees. The rainfed trees however did not reach tapping stage even after nine years of grwoth, indicating that water was the most important and theonly limiting factor in this region. In the traditional rubber growing region of India where there is no severe drought stress, the rainfed trees of the same clone attained tappable girth after nine years. Yield was significantly high in the irrigated trees grown in the North Konkan area compared to the traditional region. Thus, the results indicate that, with irrigation during summer, rubber cultivation is possible and there is faster and more uniform growth, and a higher latex yield in the non-traditional North Konkan region.